Ethylene and its crosstalk with hormonal pathways in fruit ripening: mechanisms, modulation, and commercial exploitation - Tipu, Mohammad M. H.; Sherif, Sherif M. (Frontiers in Plant Science, 2024)
Ethylene is an essential phytohormone that orchestrates a multitude of physiological and biochemical processes regulating fruit ripening, from early maturation to post-harvest. This review offers a comprehensive analysis of ethylene's multifaceted roles in climacteric fruit ripening, characterized by a pronounced increase in ethylene production and respiration rates. It explores potential genetic and molecular mechanisms underlying ethylene's action, focusing on key transcription factors, biosynthetic pathway genes, and signal transduction elements crucial for the expression of ripening-related genes. The varied sensitivity and dependency of ripening traits on ethylene are elucidated through studies employing genetic mutations and ethylene inhibitors such as AVG and 1-MCP. Additionally, the modulation of ripening traits by ethylene is influenced by its interaction with other phytohormones, including auxins, abscisic acid, gibberellins, jasmonates, brassinosteroids, and salicylic acid. Pre-harvest fruit drop is intricately linked to ethylene, which triggers enzyme activity in the abscission zone, leading to cell wall degradation and fruit detachment. This review also highlights the potential for applying ethylenerelated knowledge in commercial contexts to enhance fruit quality, control pre-harvest drop, and extend shelf life. Future research directions are proposed, advocating for the integration of physiological, genetic, biochemical, and transcriptional insights to further elucidate ethylene's role in fruit ripening and its interaction with other hormonal pathways.